Managing preconceived expectations: mental health service users experiences of going home from hospital: a grounded theory study. Issue 9 (24th August 2015) - Keogh, B.; Callaghan, P.; Higgins, A.
<x xml:space="preserve">Abstract</x> Accessible summary What is known on the subject? The time of discharge from a mental health hospital can be challenging for mental health service users, with high rates of readmission in the immediate months following discharge. Although some research exists that explores service users' perspectives of being discharged, little evidence exists that explores the processes influencing or used by service users' to adapt to the transition from in‐patient acute mental health service. What this papers adds to existing knowledge? The findings of this grounded theory study demonstrates the strategies service users used to managed their own, as well as their social audiences, preconceived expectations arising from their new identity as 'psychiatric patients' following their discharge from hospital. While there is a move to develop recovery‐orientated mental health services, key indicators of recovery‐oriented practices were often absent from service users' experiences of service provision. What are the implications for practice? Nurses and other mental health professionals need to recognize their contribution to the architecture of stigma that transcends the physical structures of hospital or ward and are entrenched within attitudes, interactions and practices. The findings of this study can provide guidance to those working with service users and help them to understand the complexities of their experiences when using mental health services, which go far beyond the management of their symptoms. Abstract Introduction Following a period of hospitalization, the transition to home can result in increased vulnerability and a source of stress for mental health service users. Readmission rates have been suggested as one indicator of the success of the transition from hospital to community care. Despite knowledge of some of the factors that impact on service users following discharge, no coherent model or theoretical framework could be located in the literature, which explains or aides an in‐depth understanding of the transition from hospital to community for service users. Aim The aim of this study was to develop a grounded theory that explored service users' experiences of going home from hospital. Method This qualitative study used grounded theory, and a total of 35 interviews were conducted with 31 service users. Results The core category was 'Managing Preconceived Expectations', which had seven subcategories, describes how the participants were negatively perceived by themselves and others following their admission and discharge from hospital. Implications for Practice This theory presents the strategies that the participants used to manage this new identity. This theory demonstrates that although there has been a move to adopt recovery‐orientated services, key indicators of recovery were often absent for service users being admitted and subsequently discharged.